Whole genome sequence of the Treponema Fribourg-Blanc: unspecified simian isolate is highly similar to the yaws subspecies - Zobaníková, Marie; Strouhal, Michal; Mikalová, Lenka; Cejková, Darina; Ambrožová, Lenka; Pospíšilová, Petra; Fulton, Lucinda L; Chen, Lei; Sodergren, Erica; Weinstock, George M; Smajs, David (PLoS neglected tropical diseases, 2013)
BACKGROUND: Unclassified simian strain Treponema Fribourg-Blanc was isolated in 1966 from baboons (Papio cynocephalus) in West Africa. This strain was morphologically indistinguishable from T. pallidum ssp. pallidum or ssp. pertenue strains, and it was shown to cause human infections. METHODOLOGY/PRINCIPAL FINDINGS: To precisely define genetic differences between Treponema Fribourg-Blanc (unclassified simian isolate, FB) and T. pallidum ssp. pertenue strains (TPE), a high quality sequence of the whole Fribourg-Blanc genome was determined with 454-pyrosequencing and Illumina sequencing platforms. Combined average coverage of both methods was greater than 500×. Restriction target sites (n = 1,773), identified in silico, of selected restriction enzymes within the Fribourg-Blanc genome were verified experimentally and no discrepancies were found. When compared to the other three sequenced TPE genomes (Samoa D, CDC-2, Gauthier), no major genome rearrangements were found. The Fribourg-Blanc genome clustered with other TPE strains (especially with the TPE CDC-2 strain), while T. pallidum ssp. pallidum strains clustered separately as well as the genome of T. paraluiscuniculi strain Cuniculi A. Within coding regions, 6 deletions, 5 insertions and 117 substitutions differentiated Fribourg-Blanc from other TPE genomes. CONCLUSIONS/SIGNIFICANCE: The Fribourg-Blanc genome showed similar genetic characteristics as other TPE strains. Therefore, we propose to rename the unclassified simian isolate to Treponema pallidum ssp. pertenue strain Fribourg-Blanc. Since the Fribourg-Blanc strain was shown to cause experimental infection in human hosts, non-human primates could serve as possible reservoirs of TPE strains. This could considerably complicate recent efforts to eradicate yaws. Genetic differences specific for Fribourg-Blanc could then contribute for identification of cases of animal-derived yaws infections.
Keywords: Treponemal Infections; genom bakteriální; zvířata; frambézie; Humans; Yaws; Genome, Bacterial; Treponema; Papio; infekce bakteriemi rodu Treponema; lidé; Animals